Integration of the ZoneBOND™ temporary bonding material in backside processing for 3D applications - Jourdain, A.; Phommahaxay, A.; Verbinnen, G.; Suhard, S.; Miller, A.; Manna, A. La; Swinnen, B.; Beyer, G.; Beyne, E. (2012 4th Electronic System-Integration Technology Conference, 2012)
Among the many 3D technology options that are being explored today, the 3D-stacked IC approach has become a mature and economically viable technology and provides the highest density for 3D interconnects to date. A key step in this process is the bonding of the device wafer to a carrier wafer prior to wafer thinning, by using a temporary adhesive layer. While great progress has been made over the past 2 years with respect to the wafer-support system, some of these materials including thermoplastics, laser-degradable or chemically dissolvable materials can present some integration limitations, especially if low-melting-point solders or high-topography structures are present on the backside of the wafers. The approach pursued by imec was for the first time demonstrated on full CMOS wafers using the BSI HT-10.10 thermoplastic material in a 300mm production line, and this work furthers the previous development by successfully demonstrating the integration of the room temperature peelable ZoneBOND temporary bonding material from Brewer Science as a one-to-one alternative to the BSI HT-10.10 material.